Prevalence and determinants of diabetes mellitus in a representative sample of Italian adults - Rosario Asciutto; Alessandra Lugo; Silvano Gallus; Maria Carla Roncaglioni; Carlo La Vecchia; Cristina Bosetti (Epidemiology, Biostatistics and Public Health)
PREVALENCE AND DETERMINANTS OF DIABETES MELLITUS IN A REPRESENTATIVE SAMPLE OF ITALIAN ADULTS Background: Diabetes mellitus is a dramatic epidemic worldwide. This study providea an updated estimate of itsprevalence and determinants among Italian adults. Methods: Data were derived from a face-to-face survey conducted in 2013 on 2901 individuals (1391 men, 1510 women) aged ≥18 years, representative of the general adult Italian population. Odds ratios (OR) for diabetes versus non diabetes in relation to selected risk factors were derived using multiple logistic regression models. Results: Overall, 135 out of 2901 adults (4.7%) reported a diagnosis of diabetes, with similar prevalence in men (4.8%) and in women (4.5%). Diabetes increased with age (0.6% at age 18-44, 5.1% at age 45-64, and 11.3% at age ≥65 years; p-trend <0.001) and decreased with increasing level of education (12.8% for low, 7.8% for middle, and 1.4% for high education; p-trend <0.001). Prevalence was higher among obese subjects (10.8%) compared to normal weight subjects (3.1%; OR=2.46; p-trend=0.001), among individuals reporting a physical activity <30 minutes of walk/day (5.6%) compared to those reporting >60 minutes of walk/day (3.8%; OR=1.43), and among ex-smokers (11.6%) compared to never smokers (4.2%; OR=2.51); moreover, it was lower among moderate drinkers (3.1%) than among abstainers (6.1%; OR=0.57; p-trend=0.016). Prevalence of diabetes was 16.1% in individuals with a diagnosis of hypertension (OR=4.66), 15.2% in those with high cholesterol (OR=3.84), and 21.6% among aspirin users (OR=4.46). Conclusion: Although diabetes prevalence in Italy is still comparatively low, effective clinical and preventive intervention strategies – focused on major risk behaviors – should be implemented to control the diffusion of this condition.